A new Cymothales Gerstaecker from the Gabonese rainforest (Neuroptera Myrmeleontidae) - Badano, Davide (Zootaxa, 2020)
Nine species of Cymothales, one of the most characteristic African antlion genera, are known from the Guineo-Congolian rainforests. A new species, Cymothales massaronei sp. nov. is described here from Gabon. Cymothales massaronei sp. nov. is characterized by the fifth tarsomere equal in length to the first tarsomere, but differs from all of the congeners with this character in the shape and markings of wings, shape of antenna and body pattern.